2018
DOI: 10.1186/s12933-018-0695-y
|View full text |Cite
|
Sign up to set email alerts
|

Empagliflozin influences blood viscosity and wall shear stress in subjects with type 2 diabetes mellitus compared with incretin-based therapy

Abstract: BackgroundCardiovascular protection following empagliflozin therapy is not entirely attributable to the glucose lowering effect. Increased hematocrit might influence the shear stress that is the main force acting on the endothelium, regulating its anti-atherogenic function.ObjectiveWe designed the study with the aim of investigating the effect of empagliflozin on blood viscosity and shear stress in the carotid arteries. A secondary endpoint was the effect of empagliflozin on carotid artery wall thickness.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 42 publications
(45 reference statements)
2
30
0
1
Order By: Relevance
“…However, our study is superior in terms of certain aspects including study design, sample size, and observation duration. Like Irace et al [39], our study reports that IMT decreased after SGLT2 inhibitor treatment compared with pretreatment. Moreover, all three studies report that SGLT2 inhibitor treatment has not been proven to significantly prevent IMT progression compared to with the conventional treatment.…”
Section: Effects Of Tofogliflozin On Atherosclerosissupporting
confidence: 80%
See 1 more Smart Citation
“…However, our study is superior in terms of certain aspects including study design, sample size, and observation duration. Like Irace et al [39], our study reports that IMT decreased after SGLT2 inhibitor treatment compared with pretreatment. Moreover, all three studies report that SGLT2 inhibitor treatment has not been proven to significantly prevent IMT progression compared to with the conventional treatment.…”
Section: Effects Of Tofogliflozin On Atherosclerosissupporting
confidence: 80%
“…Two earlier, non-randomized studies evaluated the effects of SGLT2 inhibitors on IMT in T2DM patients [ 39 , 40 ]. A 3-month prospective cohort study with 35 Italian T2DM patients by Irace et al [ 39 ] showed that empagliflozin and incretin-based therapy reduced IMT. However, it did not evaluate potential differences in IMT reduction between groups, and was limited by small sample size and short treatment duration.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these data suggest that dapagliflozin might indeed be superior to sitagliptin for the cardiometabolic effects. In addition, previous studies reported the preferable cardiometabolic effects regarding SGLT2 inhibitors [36][37][38][39]. Dapagliflozin also showed stronger therapeutic effects on other indices that might contribute to the prevention of cardiovascular events.…”
Section: Discussionmentioning
confidence: 87%
“…A meta-analysis of 5 studies found that 3–12 months of GLP-1 based therapies decreased cIMT, although statistically non-significantly [71]. A prospective cohort study of 35 type 2 diabetes outpatients found significantly reduced IMT in the empagliflozin and liraglutide-treated patients after 3 months of treatment [72]. Sitagliptin and liraglutide treatment also improved arterial stiffness, diastolic function and myocardial strain by reducing oxidative stress in subjects with newly diagnosed type 2 diabetes [73, 74].…”
Section: Discussionmentioning
confidence: 99%